Application of blocked isocyanate in preparation of polyurethane(urea) elastomers. Issue 24 (10th February 2021) - Sang, Shilin; Li, Yuanyuan; Wang, Kaijie; Tang, Jialing
Abstract: High‐performance casting polyurethane elastomers (CPUe) were successfully synthesized by the reaction of polyurethane prepolymer (PUP) blocked by methyl ethyl ketone oxime (MEKO) with diamine chain extenders. The effects of blocking agent were systematically studied on the structures, thermal stabilities, mechanical properties, and processability of polyurethane. The addition of MEKO significantly improved the tensile strength and toughness. The maximum tensile strength was 35.6 MPa, and the maximum elongation at break was 1065%. The high strength and toughness were attributed to the fact that under mild reaction conditions, the reaction tended to extend the molecular chains, which indicated that the formation of long chains was conducive to the extension and self‐reinforcement of chain segments. Crystallization and strong hydrogen bonds between molecules also led to low loss factor. This deblocking polymerization strategy solves the gel problem in the polymerization process, and provides a new idea for the preparation of CPU. Abstract : The blocking agent method was applied to casting polyurethane elastomer (CPU), which solved the problem of gelation of high‐reactivity chain extenders in the reaction. Compared with the traditional solution method, the product obtained by this method can simultaneously increase the strength and elongation. 4, 4'‐Diaminodiphenylmethan with regular structure was used as a chain extender to synthesize a polyurethane elastomer with good microphase separation, and the best chain extender ratio was determined